ESTIMATION OF UNCERTAINTY IN DUCTILITY AND HARDNESS OF STEELS - Basilio Pires Nonato, Raphael; Signorelli, Eduardo de Assunção (Revista Ciências Exatas, 2017)
The fact that the world is now inserted in the context of the dynamism arising from the globalization, in which great part of its nations is interconnected, forces the companies to be more competitive when searching for customers. One of the ways to achieve competitiveness is by considering the uncertainties related to materials properties, which can lead the company to offer its product in a safer condition, contributing to the maintenance and growing of its reliability and, consequently, to the long-term relationship with the customer. The general objective of this paper is to point out a method to consider the uncertainties overall the process of obtaining ductility and hardness of steels. This research has theoretical character with quantitative approach, making use of literature review, resulting in a table containing generator factors, types, quantification methodology, and coverage factors of uncertainties related to the abovementioned properties.